Helping Adolescents with Greater Psychosocial Needs: Subjective Outcome Evaluation Based on Different Cohorts - Daniel T. L. Shek; Tak Yan Lee (The Scientific World Journal)
The Tier 2 Program of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) is designed to help students with greater psychosocial needs. This paper examines nine sets of subjective outcome evaluation data collected from 2005 to 2009 (n=60,241 participants). Based on the consolidated data with schools as units, results showed that participants generally had positive perceptions of the program, implementers, and benefits of the program. The subjective outcome evaluation instrument was found to be internally consistent. Multiple regression analysis revealed that perceived qualities of the program and the program implementers predicted perceived effectiveness of the program. The present study provides support for the effectiveness of the Tier 2 Program of the Project P.A.T.H.S. in Hong Kong.